Risk factors for reporting adverse events and for study withdrawal in a population-based trial of vitamin D supplementation. Issue 197 (March 2020) - Malihi, Z; Wu, Z; Lawes, CMM; Sluyter, J; Waayer, D; Toop, L; Khaw, K-T; Camargo, CA; Scragg, R
Highlights: Adverse events are routinely monitored in randomized controlled trials. However, the factors associated with adverse events have rarely been studied. We analyzed self-reported adverse events in a large vitamin D supplement trial. There was no pattern in the factors associated with self-reported adverse events. Adverse events were not associated with risk of withdrawal from the study. Abstract: With increasing numbers of randomized controlled trials (RCTs) investigating potential health events of vitamin D supplementation, a better understanding is required of the risk factors for adverse events and for study withdrawals. This analysis aimed to identify baseline risk factors of reporting an adverse event in a multi-year randomized double-blinded placebo-controlled trial of vitamin D supplementation. The secondary aim was to investigate if adverse events were associated with study withdrawals. We analyzed data from the Vitamin D Assessment (ViDA) study: 5110 adults, aged 50–84 years, living in Auckland, New Zealand. Monthly doses of 100, 000 IU vitamin D3 or placebo were mailed to participants homes, with a questionnaire to collect data on adverse events and adherence to the study capsule (initially monthly, then 4-monthly). Median follow-up was 3.3 years. Data were analysed using multivariable log-binomial regression and Cox-regression. During the follow-up period, 818 people reported adverse events and 412 withdrew or stopped returning questionnaires. Vitamin D was not associated with reporting of adverse events. Of sociodemographic factors, ethnicity was associated with reporting adverse events: compared to European participants, Maori and Pacific Islander people were more likely to report an adverse event. Non-smokers were more likely to report an adverse event, compared to smokers (adjusted hazard ratio (HR) = 1.80; 95%CI = 1.24, 2.62); as were those who had reported a history of depression (adjusted HR = 1.27; 95%CI = 1.01, 1.60) or a recent cough or cold (adjusted HR = 1.22; 95%CI = 1.03, 1.44) at baseline. Reporting of adverse events was not associated with withdrawals (adjusted HR = 1.12; 95%CI = 0.86, 1.46). These data did not identify any clear pattern in the factors associated with self-reported adverse events, which themselves did not increase risk of withdrawals.